Association of adverse childhood experiences and precuneus volume with intrusive reexperiencing in autism spectrum disorder. Issue 9 (29th June 2021) - Kitamura, Soichiro; Makinodan, Manabu; Matsuoka, Kiwamu; Takahashi, Masato; Yoshikawa, Hiroaki; Ishida, Rio; Kishimoto, Naoko; Yasuno, Fumihiko; Yasuda, Yuka; Hashimoto, Ryota; Miyasaka, Toshiteru; Kichikawa, Kimihiko; et al.
Abstract: Compared to typically developing (TD) children, people with autism spectrum disorder (ASD) have an increased risk of adverse childhood experiences (ACEs). Exposure to ACEs is associated with adult ASD psychological comorbidities, such as posttraumatic stress disorder (PTSD). Occurrence of intrusive event reexperiencing, characteristic of PTSD, often causes social dysfunction in adults with ASD, but its pathological basis is unclear. This study examined brain regions related to the severity of intrusive reexperiencing and explored whether ACE severity was associated with that of intrusive reexperiencing and/or extracted regional gray matter volume. Forty‐six individuals with ASD and 41 TD subjects underwent T1‐weighted magnetic resonance imaging and evaluation of ACEs and intrusive reexperiencing. Brain regions related to the severity of intrusive reexperiencing in both groups were identified by voxel‐based whole brain analyses. Associations among the severity of intrusive reexperiencing, that of ACEs, and gray matter volume were examined in both groups. The severities of intrusive reexperiencing and ACEs were significantly associated with reduced gray matter volume in the right precuneus in individuals with ASD but not in TD subjects. Although the right precuneus gray matter volume was smaller in individuals with ASD and severe ACEs than in those with mild ACEs or TD subjects, it was similar in the latter two groups. However, ACE‐dependent gray matter volume reduction in the right precuneus led to intrusive reexperiencing in individuals with ASD. This suggests that exposure to ACEs is associated with right precuneus gray matter reduction, which is critical for intrusive reexperiencing in adults with ASD. Lay Summary: Individuals with autism spectrum disorder (ASD) are at increased risk of adverse childhood experiences (ACEs) and of subsequent manifestation of intrusive reexperiencing of stressful life events. The present study found that reduced gray matter volume in the right precuneus of the brain was associated with more severe intrusive reexperiencing of ACEs by individuals with ASD. These results suggest that ACEs affect neural development in the precuneus, which is the pathological basis of intrusive event reexperiencing in ASD.